2013
DOI: 10.1002/srin.201300157
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Investigations of Inclusions in Ferroalloys

Abstract: As the requirements on material properties increase, there has been a demand on an additional knowledge on the effect of impurities in the ferroalloys on the properties. Thus, the number, morphology, size, and composition of inclusions in four different ferroalloys (FeTi, FeNb, FeSi, and SiMn) were investigated. This was done in three dimensions (3D) by using scanning electron microscopy in combination with energy dispersive spectroscopy after electrolytic extraction of the ferroalloy samples. The non‐metallic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 19 publications
2
24
1
1
Order By: Relevance
“…It was found that the composition and size ranges of non‐metallic inclusions observed in the FeTi70R alloy in this study are quite different in comparison to the results for the FeTi70 alloy published in previous studies . This may be explained by the different quality of raw materials and the different technology methods for production of the investigated ferroalloys at the different companies.…”
Section: Resultscontrasting
confidence: 83%
See 1 more Smart Citation
“…It was found that the composition and size ranges of non‐metallic inclusions observed in the FeTi70R alloy in this study are quite different in comparison to the results for the FeTi70 alloy published in previous studies . This may be explained by the different quality of raw materials and the different technology methods for production of the investigated ferroalloys at the different companies.…”
Section: Resultscontrasting
confidence: 83%
“…Non‐metallic inclusions in different ferroalloys such as FeTi, FeNb, FeSi, and FeMn have been investigated in previous studies . It was reported that FeTi70 alloys contain different types of non‐metallic inclusions, which are listed in Table .…”
Section: Introductionmentioning
confidence: 99%
“…1,14,15 Overall, the inclusions can be divided into two broad categories depending on whether the melting point of the inclusions lies below or above the freezing point of the liquid steel, as shown in Table 7. Here, the mechanism of the dissolution of class I and II inclusions are totally different.…”
Section: Discussionmentioning
confidence: 99%
“…Bi et al 41) investigated the inclusions from samples of an experiment with nozzle clogging. The typical SEM pictures of the inclusions and clusters from a film filter after electrolytic extraction of the samples are shown in Fig.…”
Section: Experimental Datamentioning
confidence: 99%